2000
DOI: 10.1128/jvi.74.18.8444-8451.2000
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor-Independent Proliferation of Erythroid Cells Infected with Friend Spleen Focus-Forming Virus Is Protein Kinase C Dependent but Does Not Require Ras-GTP

Abstract: Interaction of erythropoietin (Epo) with its cell surface receptor activates signal transduction pathways which result in the proliferation and differentiation of erythroid cells. Infection of erythroid cells with the Friend spleen focus-forming virus (SFFV) leads to the interaction of the viral envelope glycoprotein with the Epo receptor and renders these cells Epo independent. We previously reported that SFFV induces Epo independence by constitutively activating components of several Epo signal transduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 75 publications
1
30
0
1
Order By: Relevance
“…These ®ndings imply that basal activity of Ras/ERK signaling pathway plays a major role in preventing di erentiation and sustaining proliferative potential of these cells. Muszynski et al (1998) recently reported that Friend murine leukemia virus (FV) may elevate the basal activity of Raf-1/MAPK pathway in infected cells, which o ers an interesting hypothesis on the molecular mechanism of leukemogenesis by this virus. Consistent with this hypothesis, we observed that super-activation of Ras/ERK signaling pathway, through expression of Ras12V or MAPKKm, prevented the di erentiation induced by EPO, DMSO, or n-butyrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ®ndings imply that basal activity of Ras/ERK signaling pathway plays a major role in preventing di erentiation and sustaining proliferative potential of these cells. Muszynski et al (1998) recently reported that Friend murine leukemia virus (FV) may elevate the basal activity of Raf-1/MAPK pathway in infected cells, which o ers an interesting hypothesis on the molecular mechanism of leukemogenesis by this virus. Consistent with this hypothesis, we observed that super-activation of Ras/ERK signaling pathway, through expression of Ras12V or MAPKKm, prevented the di erentiation induced by EPO, DMSO, or n-butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…Transient activation of Jak/ STAT pathway as well as Ras/MAP kinase (MAPK) pathways after EPO-stimulation has been documented (Miura et al, 1994;Sawyer and Penta, 1996;Quelle et al, 1996;Torti et al, 1992;Todokoro et al, 1994;Tilbrook et al, 1996;Gobert et al, 1995;Nagata et al, 1997). Among various EPO-dependent cell lines, good correlation has been observed between the basal activity of these signaling pathways and the proliferative potential of the cells (Gobert et al, 1995;Tilbrook et al, 1996;Miura et al, 1994;Carroll and May, 1994;Muszynski et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…35,36 However, experiments described in these reports used Spi-1 overexpression in erythroleukemic cells harboring a deregulation in Epo/EpoR signaling, 34,37,38 thus impeding a clear definition of the contribution of Spi-1 in the differentiation blockage. In contrast, preleukemic proerythroblasts derived from spi-1 transgenic mice as used in the present study are dependent on Epo for their survival and growth, and Epo signaling is normal in that cells.…”
Section: Discussionmentioning
confidence: 99%
“…A functional F-gp55 activated EpoR signal was required for PU.1 transcriptional upregulation in Friend erythroleukemia cells Accumulating evidence indicates that F-gp55 activated EpoR signals di er from Epo activated EpoR signals (Tarr et al, 1997;Muszynski et al, 2000;Nishigaki et al, 2000). Speci®cally F-gp55/EpoR activated PKC activity is required for proliferation of Friend erythroleukemia cells .…”
Section: Resultsmentioning
confidence: 99%
“…Panel on the right is an immunoblot analysis for PU.1 protein levels in cells following Zn treatment (+) or without Zn treatment (7). Equal amounts of total protein were loaded in each lane way, the lipid phosphatase SHIP, and PKC occur in SFFV infected erythroid cells, tyrosine phosphorylation of the EpoR and activation of JAK2 appear to not be required for proliferation of SFFV infected cells (Muszynski et al, 1998;Muszynski et al, 2000;Nishigaki et al, 2000). Activation of PI3K signaling pathways in SFFV infected cells occurs through tyrosine phosphorylated Insulin Receptor SubstrateRelated (IRS) adapter proteins (Nishigaki et al, 2000).…”
Section: Discussionmentioning
confidence: 99%